2012
DOI: 10.1016/j.meegid.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology, population genetics, and pathogenic role of Helicobacter pylori

Abstract: Helicobacter pylori infection is linked to various gastroduodenal diseases; however, only approximately 20% of infected individuals develop severe diseases. Despite the high prevalence of H. pylori infection in Africa and South Asia, the incidence of gastric cancer in these areas is much lower than in other countries. Furthermore, the incidence of gastric cancer tends to decrease from north to south in East Asia. Such geographic differences in the pathology can be explained, at least in part, by the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 100 publications
5
94
1
6
Order By: Relevance
“…Studies have found that in Western countries, strains containing the s1m1 genotype are associated with a higher risk of gastric disease, as well as with enhanced proinflammatory response [17]. Similar to our results, Asrat, et al [18] and Suzuki, et al [19] also found s1m1 to be the most common vacA genotype. Interestingly, all of these virulence factors have a mutual relationship; for example, cagA-positive strains often have the s1m1 genotype, and several studies have provided evidence of an association between the cagA+/vacA s1m1 genotype and the risk of gastric disease, which was also found in our study [20] [21] [22].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have found that in Western countries, strains containing the s1m1 genotype are associated with a higher risk of gastric disease, as well as with enhanced proinflammatory response [17]. Similar to our results, Asrat, et al [18] and Suzuki, et al [19] also found s1m1 to be the most common vacA genotype. Interestingly, all of these virulence factors have a mutual relationship; for example, cagA-positive strains often have the s1m1 genotype, and several studies have provided evidence of an association between the cagA+/vacA s1m1 genotype and the risk of gastric disease, which was also found in our study [20] [21] [22].…”
Section: Discussionsupporting
confidence: 91%
“…However, the incidence of gastric cancer is enigmatically low in Africa and South Asia, where frequency of H pylori infection is high. Furthermore, several studies from East Asia and Iran have indicated a tendency towards reduction of GC incidence from north to south within these areas (Suzuki et al, 2012;Latifi-Navid et al, 2013). H pylori virulence factors have been shown to play an important role in determining the course of H pylori associated disease (Suerbaum and Michetti, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Özellikle kronik atrofik gastrit, peptik ülser ve gastrik kanser gibi gastrointestinal sistem hastalıkları başta olmak üzere romatolojik, hematolojik ve dermatolojik hastalıklar gibi birçok gastrointestinal sistem dışı hastalığında etyopatogenezinde suçlanmaktadır (1). Vac-A(vacuolating cytotoxin) ve Cag-A, HP suşları nın ürettiği ve bakteri virulansından sorumlu olan iki önemli sitotoksindir (13). Bu sitotoksinler içinde Cag-A özellikle doğu ülkelerinde dü-şük sıklıkta saptanmaktadır ve gastrointestinal dışı hastalıklar ve komplikasyonlardan temel olarak sorumlu tutulmaktadır (13).…”
Section: Discussionunclassified
“…Vac-A(vacuolating cytotoxin) ve Cag-A, HP suşları nın ürettiği ve bakteri virulansından sorumlu olan iki önemli sitotoksindir (13). Bu sitotoksinler içinde Cag-A özellikle doğu ülkelerinde dü-şük sıklıkta saptanmaktadır ve gastrointestinal dışı hastalıklar ve komplikasyonlardan temel olarak sorumlu tutulmaktadır (13). Literatürde; AA'nın etyolojisinde HP'nin ilişkili olabileceğini gösteren çelişkili sonuçlar bulunmaktadır (14,15).…”
Section: Discussionunclassified